2008
DOI: 10.1007/s11248-008-9204-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered renal morphology in transgenic mice with cholecystokinin overexpression

Abstract: Although cholecystokinin is a regulatory peptide with a predominant role in the brain and the gastrointestinal tract, there is an increasing evidence for its role in the kidney. The aim of this study was to reveal morphological changes in the structure of kidney of mice with cholecystokinin overexpression by means of light, transmission and scanning electron microscope, and atomic force microscopy. Using immunohistochemistry the expression of important basement membrane proteins collagen IV, laminin and fibron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Aunapuu et al (42) recently reported that CCK overexpression was associated with renal morphological damage in transgenic mice without a significant difference in kidney weight or proteinuria, but with a thickened glomerular basement membrane. CCK is expressed from embryonic day (E) 8.5, whereas both CCK-1R and CCK-2R have been identified from E10.5; in addition, CCK is thought to affect tissue growth and differentiation (43).…”
Section: Discussionmentioning
confidence: 99%
“…Aunapuu et al (42) recently reported that CCK overexpression was associated with renal morphological damage in transgenic mice without a significant difference in kidney weight or proteinuria, but with a thickened glomerular basement membrane. CCK is expressed from embryonic day (E) 8.5, whereas both CCK-1R and CCK-2R have been identified from E10.5; in addition, CCK is thought to affect tissue growth and differentiation (43).…”
Section: Discussionmentioning
confidence: 99%
“…As classical gut hormones and potent neurotransmitters, gastrin and CCK are widely distributed in gastrointestinal tract, CNS, and peripheral neurons (4,18). However, CCK has also been suggested to stimulate spermatozoan fertilization, exert anti-inflammatory effects, promote sodium excretion into the urine, and predict the risk of mortality in heart failure, consistent with its expression in male germ cells (19), cells of immune system (20)(21)(22)(23), renal cortex and medulla (24), and cardiomyocytes (25), respectively.…”
Section: Gastrin and Cckmentioning
confidence: 95%
“…The extent of mesangial expansion of each group was calculated as sums of the score of each proliferation degree [11]. Tubular damage was evaluated according to the degrees of hyaline degeneration of tubular epithelial cells and quantitatively scored in each group as previously described [12]. …”
Section: Methodsmentioning
confidence: 99%